Analisis Hakikat Keterampilan Menulis Lanjutan Pada Kelas Tinggi - Juni Sahla Nasution; Ainun Mardiah; Khairunnisa Khairunnisa; Trisna Pratiwi Hasibuan; Yuli Deliyanti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The aim of this research is to find the problems of advanced writing skills of upper elementary school students, and provide solutions. The research method used is a literature review. Based on the research results, it can be concluded that there are two factors that cause students' difficulties in writing at a high level, namely internal factors and external factors. Internal factors include students' weak motor skills, weak visual memory, low students' interest and motivation to learn, and finally students' study habits in class and at home. Meanwhile, external factors include lack of attention from parents towards students, an atmosphere at home that is less supportive, environmental conditions and finally the influence of social media. The lack of writing skills in elementary school students may also be caused by the less than optimal use of innovative learning methods. One way to optimize the writing learning process and increase students' writing motivation is to increase students' interest in writing through interesting learning models and learning media.